2022
DOI: 10.1002/cam4.5445
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' perceived barriers and facilitators of health behavior support provision: A qualitative study

Abstract: Background: Childhood cancer survivors (CCSs) have an increased risk of developing chronic health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This review highlights the importance of increasing knowledge about healthy behaviors in general among CAYA cancer survivors through health behavior advice, information dissemination, and health promotion discussions with HCPs. These findings align with a recent qualitative study of HCPs, which highlighted the critical role of education and training of HCPs in effectively guiding CAYA cancer survivors toward healthy behaviors 68 . Survivorship care clinics should prioritize the integration of health behavior support services such as lifestyle coaching and ensure that HCPs are adequately equipped with the necessary knowledge and skills to support survivors in adopting and maintaining healthy behaviors.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This review highlights the importance of increasing knowledge about healthy behaviors in general among CAYA cancer survivors through health behavior advice, information dissemination, and health promotion discussions with HCPs. These findings align with a recent qualitative study of HCPs, which highlighted the critical role of education and training of HCPs in effectively guiding CAYA cancer survivors toward healthy behaviors 68 . Survivorship care clinics should prioritize the integration of health behavior support services such as lifestyle coaching and ensure that HCPs are adequately equipped with the necessary knowledge and skills to support survivors in adopting and maintaining healthy behaviors.…”
Section: Discussionsupporting
confidence: 80%
“…These findings align with a recent qualitative study of HCPs, which highlighted the critical role of education and training of HCPs in effectively guiding CAYA cancer survivors toward healthy behaviors. 68 Survivorship care clinics should prioritize the integration of health behavior support services such as lifestyle coaching and ensure that HCPs are adequately equipped with the necessary knowledge and skills to support survivors in adopting and maintaining healthy behaviors. In addition, a systematic review of 17 randomized controlled trials among all types of patients showed that using deliberate communication strategies when providing information can improve patient outcomes more effectively than not using such strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A healthy lifestyle including regular physical activity and nutrient and vitamin rich diet can reduce this risk (36). It is important to include health care professionals in survivorship care to support a healthy lifestyle among this cohort (37). Generally, due to limited resources, regular lifestyle counseling might not be feasible for every CCS during LTFU which is why it is particularly important to identify CCS at risk for metabolic complications.…”
Section: Discussionmentioning
confidence: 99%